Dynamism of PI4-Phosphate during Interactions with Human Erythrocytes in Entamoeba histolytica - Natsuki Watanabe (Microorganisms, 2020)
Phosphatidylinositol phosphates (PIPs) are involved in many cellular events as important secondary messengers. In Entamoeba histolytica, a human intestinal protozoan parasite, virulence-associated mechanisms such as cell motility, vesicular traffic, trogo- and phagocytosis are regulated by PIPs. It has been well established that PI3P, PI4P, and PI(3,4,5)P3 play specific roles during amoebic trogo- and phagocytosis. In the present study, we demonstrated the nuclear localization of PI4P in E. histolytica trophozoites in steady state with immunofluorescence imaging and immunoelectron microscopy, using anti-PI4P antibodies and PI4P biosensors [substrate of the Icm/ Dot type IV secretion system (SidM)]. We further showed that the nuclear PI4P decreased after a co-culture with human erythrocytes or Chinese hamster ovary (CHO) cells. However, concomitant changes in the localization and the amount of PI(4,5)P2, which is the expected major metabolized (phosphorylated) product of PI4P, were not observed. This phenomenon was specifically caused by whole or ghost erythrocytes and CHO cells, but not artificial beads. The amount of PIP2 and PIP, biochemically estimated by [32P]-phosphate metabolic labeling and thin layer chromatography, was decreased upon erythrocyte adherence. Altogether, our data indicate for the first time in eukaryotes that erythrocyte attachment leads to the metabolism of nuclear PIPs, and metabolites other than PI(4,5)P2 may be involved in the regulation of downstream cellular events such as cytoskeleton rearrangement or transcriptional regulation.